If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3y = 3 Solving 4x + 3y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 4x + 3y + -3y = 3 + -3y Combine like terms: 3y + -3y = 0 4x + 0 = 3 + -3y 4x = 3 + -3y Divide each side by '4'. x = 0.75 + -0.75y Simplifying x = 0.75 + -0.75y
| X^2-4x+2=0 | | 7y-4y=6 | | 2(x-4)=24 | | 5x(x+2)+6=3 | | -x+11=-2.4+x | | -10-3x=3x+2 | | (n-6)*4=8 | | (n+5)*3=21 | | 4(3r+2)-3r=-10 | | 16=10+2m | | -3x-5+6x= | | -40-(2x+5)=-6 | | (6x+5)+(5x-12)=180 | | 1.3y=9 | | 2y+4=3y-9 | | 46-(4x+4)=4(x+6)+x | | 4z-1=11 | | 6-3x=-18x | | 8x+3=4x-13 | | 42x-6-4x+2= | | -5(2w+1)=25 | | -22=(x-4) | | -12=6x-12 | | 5c-15=2c+6 | | 8c=5c+21 | | 8-x=3x+2(x-4) | | 10n^2-35=65n | | 3y-5+y+45=6y+40-4y | | -7-x=-11-2x | | 4x+2=3x-3 | | b^2+b=2 | | (3x-4)*2(x-6)*4(x+1)*(x+3)*6x= |